2004
DOI: 10.1111/j.1945-5100.2004.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on martian crustal magnetization near large impact basins

Abstract: Abstract-Martian crust endured several large meteoroid impacts subsequent to the demise of an early global magnetic field. Shock pressures associated with these impacts demagnetized parts of the crust, to an extent determined by shock resistance of magnetic materials in the crust. Impacts that form large basins generate pressures in excess of 1 GPa within a few crater radii of their impact sites. Crustal materials near the surface experience significantly reduced impact pressure, which varies with depth and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 37 publications
3
57
0
Order By: Relevance
“…Note that there is an unaccounted absence of magnetic anomalies (which could be due to smaller block sizes containing coherent magnetization) around its basin. However the presence of strong anomalies in proximity of this basin reveals a resistance against impact demagnetization supporting large crustal magnetic coercivity (Kletetschka et al 2004b). The pressure gradient that must have occurred during the impact event was estimated while considering the impact basin diameter and the evidence of presence of large magnetic anomalies indicates anomalous resistance against impact demagnetization-large crustal magnetic coercivity.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Note that there is an unaccounted absence of magnetic anomalies (which could be due to smaller block sizes containing coherent magnetization) around its basin. However the presence of strong anomalies in proximity of this basin reveals a resistance against impact demagnetization supporting large crustal magnetic coercivity (Kletetschka et al 2004b). The pressure gradient that must have occurred during the impact event was estimated while considering the impact basin diameter and the evidence of presence of large magnetic anomalies indicates anomalous resistance against impact demagnetization-large crustal magnetic coercivity.…”
Section: Introductionmentioning
confidence: 92%
“…2; Fig. 1 in Kletetschka et al [2004b]). Note that there is an unaccounted absence of magnetic anomalies (which could be due to smaller block sizes containing coherent magnetization) around its basin.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Srnka et al (1979) showed the acquisition of SRM by an impact of aluminum and basalt at velocity of 13-15 km/s. Kletetschka et al (2004) showed that pressures of about 1 GPa are sufficient to partially demagnetize all of magnetite, hematite, and titanohematite. Wasilewski (1976Wasilewski ( , 1977 and Dickinson and Wasilewski (2000) reported remanent magnetization acquired by shock to 5 GPa in magnetic and nonmagnetic environments using samples containing precipitated grains of anti-ferromagnetic iron (nonmagnetic fcc-phase) in a copper field.…”
Section: Introductionmentioning
confidence: 99%